Surface treatment method for enhancing adhesive force of gold coating on quartz surface

By growing silicon nanostructures on the surface of quartz and forming a gold coating, the problem of insufficient adhesion of the surface of quartz gold coating in the prior art is solved, and stronger adhesion and lower equipment operation cost are achieved.

CN119530799AActive Publication Date: 2025-02-28ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT

Patent Information

Application Number
CN202411661903.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The prior art has shortcomings in enhancing the adhesion of gold coatings on the surface of quartz, especially under high temperature conditions, the gold coating is prone to fall off, resulting in an increase in equipment operation cost.

Method used

Using bottom-up nanostructure growth technology, catalytic metal particles are deposited on the surface of quartz, the oxide layer is removed, the silicon nanostructure is grown, and a gold coating is formed through high-temperature oxidation and heat treatment to enhance adhesion.

Benefits of technology

By forming a large number of mechanical bite cooperation points and mechanical interlocking structures, the adhesion of the gold coating on the surface of quartz is significantly improved, the risk of coating falling off is reduced, and the equipment operation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530799A_ABST
    Figure CN119530799A_ABST
Patent Text Reader

Abstract

The invention provides a surface treatment method for enhancing adhesive force of a gold coating on a quartz surface. The surface treatment method comprises the following steps: (1) depositing catalytic metal particles on a cleaned quartz plate; (2) removing an oxide layer on the surface of the catalytic metal particles on the quartz plate obtained in the step (1); (3) growing a silicon nanostructure on the surface of the quartz plate obtained in the step (2) by using silane gas; (4) performing high-temperature oxidation on the quartz plate obtained in the step (3), so that the silicon nanostructure is changed into silicon oxide; (5) coating the surface of the quartz plate obtained in the step (4) with organic gold paste; and (6) carrying out heat treatment on the quartz plate obtained in the step (5) to decompose the organic gold on the surface to form the gold coating. According to the method, the morphology of the nanostructure can be effectively regulated and controlled, and the grown nanostructure can form a large number of mechanical occlusion action points, so that a mechanical interlocking structure can be formed with the gold coating, and the adhesive force of the gold coating on the quartz surface is effectively enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface engineering, and in particular relates to a surface treatment method for enhancing the adhesion of a gold coating on a quartz surface. Background Art

[0002] The semiconductor epitaxial process is a key step in manufacturing high-performance devices and chips, and is usually carried out in a quartz epitaxial reactor. Since high-purity quartz has good light transmittance in the near-infrared region, if there is no appropriate reflective coating, most of the heat generated by the heated base will be dissipated outside the reaction chamber in the form of thermal radiation. In addition, the greater the temperature difference between the upper and lower surfaces of the epitaxial substrate, the more serious the substrate warping, which causes crystal slip in the epitaxial layer, resulting in crystal defects and a decrease in device yield. Therefore, a certain thickness of gold coating is usually covered on the surface of the quartz epitaxial reaction chamber to reflect the infrared radiation generated by the base back into the reaction chamber, reduce energy loss, reduce the temperature difference between the upper and lower surfaces of the substrate, and improve the quality of the epitaxial layer.

[0003] In the silicon epitaxial process, the temperature of the side wall of the reaction chamber is between 300-600°C. Due to the large difference in thermal expansion coefficients between gold and quartz, gold has poor adhesion to the quartz surface, causing the gold coating on the quartz surface to easily fall off, greatly increasing the operating cost of the equipment.

[0004] Generally, surface treatment is used to increase the roughness of the quartz surface, thereby increasing the coating contact area or forming a mechanical bite effect to enhance the coating adhesion. Sandblasting is a commonly used surface treatment technology, but it will cause great damage to the quartz substrate and the ability to control the surface structure is insufficient; chemical corrosion methods can also enhance the surface roughness, but it involves strong acids and strong alkalis, which is more polluting and the controllability of the surface structure is poor.

[0005] Patent application with publication number CN104176943A discloses a method for increasing the etching roughness of a quartz wafer surface. The method first evaporates a metal masking layer on the surface of the quartz wafer, and then etches the surface of the quartz wafer using a reactive ion etcher to obtain a quartz wafer with a rough surface, thereby increasing the etching roughness of the quartz wafer surface.

[0006] Currently, most commonly used surface structure treatment methods are top-down technologies with weak structural control capabilities. They only increase the roughness of the substrate and it is difficult to obtain a structure that can form a mechanical bite effect. For coatings that are difficult to form a strong bond, such as quartz and gold coatings, the adhesion enhancement effect is limited.

[0007] Patent application with publication number EP0237206A2 discloses a process for forming a highly reflective gold coating on quartz. The application vapor-deposit a thin gold-chromium coating on quartz, then vapor-deposit a pure gold layer, and then apply a polymer protective layer, and then heat the chromium to form an interfacial oxide to enhance the adhesion of the gold-chromium layer to the quartz and solidify the polymer. The gold-chromium coating of the application has excellent adhesion between the quartz and gold coating structures, and the polymer can protect the gold coating from mechanical wear and erosion (such as water and heat erosion), but there is still room for improvement in enhancing the adhesion of the gold coating on the quartz surface. Summary of the invention

[0008] In order to solve the above problems existing in the prior art, the present invention provides a surface treatment method for enhancing the adhesion of the gold coating on the quartz surface, comprising the following steps:

[0009] (1) Depositing catalytic metal particles on a cleaned quartz plate;

[0010] (2) removing the oxide layer on the surface of the catalytic metal particles on the quartz plate obtained in step (1);

[0011] (3) using silane gas to grow a silicon nanostructure on the surface of the quartz wafer obtained in step (2);

[0012] (4) oxidizing the quartz plate obtained in step (3) at high temperature to convert the silicon nanostructure into silicon oxide;

[0013] (5) coating the organic gold paste on the surface of the quartz plate obtained in step (4);

[0014] (6) The quartz plate obtained in step (5) is subjected to heat treatment to decompose the organic gold on the surface to form a gold coating.

[0015] Preferably, the catalytic metal in step (1) is one or more of tin, indium, gallium and gold.

[0016] Preferably, in step (1), the catalytic metal is deposited on the quartz plate by thermal evaporation.

[0017] Preferably, the thickness of the catalytic metal film in step (1) is 3-5 nm, more preferably 3 nm. The thickness of the catalytic metal film is regulated by the coating process parameters. The thickness of the catalytic metal film will affect the particle diameter of the catalytic metal, and further affect the diameter and height of the silicon nanostructure.

[0018] Preferably, steps (2) and (3) are performed in a plasma enhanced chemical vapor deposition system.

[0019] Preferably, the process conditions in step (2) are: temperature of 150-250°C, more preferably 200°C; hydrogen flow rate of 15-25 SCCM, more preferably 20 SCCM; RF power of 5-15 mW / cm 2 , more preferably 10 mW / cm 2 The chamber pressure is 20-50 Pa, preferably 30 Pa; the hydrogen plasma treatment time is 5-10 min, preferably 5 min. The change of process parameters will affect the size of the generated silicon nanostructure.

[0020] Preferably, the process conditions in step (3) are: hydrogen flow rate is 50-70 SCCM, more preferably 60 SCCM; silane flow rate is 5-10 SCCM, more preferably 6 SCCM; chamber temperature is 300-400°C, more preferably 350°C; RF power density is 15-35 mW / cm 2 , more preferably 20 mW / cm 2 ; The chamber pressure is 80-120Pa, preferably 100Pa; The nanostructure growth time is 5-10min, preferably 5min. The change of process parameters here will also affect the size of the generated silicon nanostructure. By controlling the hydrogen flow rate, the reaction rate can be controlled and the quality of the nanostructure can be improved.

[0021] Preferably, the silane gas in step (3) is monosilane (SiH 4 )gas.

[0022] Preferably, in step (4), the sample is transferred to a muffle furnace, the temperature is set to 900-1000°C, more preferably 900°C; annealed in air for 50-100 min, more preferably 60 min; and the silicon nanostructure is oxidized. The temperature affects the oxidation time of the nanostructure, and the lower the temperature, the longer the oxidation time required.

[0023] Preferably, the organic gold paste in step (5) comprises resin acid gold, metal additives, resin and solvent, and the organic gold paste is coated on the treated sample surface by brushing or spraying.

[0024] Preferably, the heat treatment method in step (6) is high temperature annealing or infrared heating.

[0025] Preferably, the heat treatment method in step (6) is high temperature annealing, the high temperature annealing temperature is 750-850°C, more preferably 800°C; the high temperature annealing time is 10-15min, more preferably 15min; the heating rate is 10°C / min.

[0026] The beneficial effects of the present invention are as follows:

[0027] The present invention provides a surface treatment method for enhancing the adhesion of a gold coating on a quartz surface, which adopts a bottom-up nanostructure growth technology to effectively control the morphology of the nanostructure. Under the premise of not affecting the optical properties of the coating, a large number of mechanical bite points are formed on the silicon nanostructure, so that the silicon nanostructure grown on the quartz surface can form a large number of mechanical interlocking structures with the gold coating, effectively enhancing the adhesion of the gold coating on the quartz surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 1 and 2 are plan and side views of the quartz surface nanostructure in Example 1 of the present invention.

[0029] Figure 2 The microstructure diagram of the gold coating on the quartz surface in Example 1 and Comparative Example 1.

[0030] Figure 3 The graph is a measurement result of the adhesion strength of the gold coating in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0031] Example 1

[0032] The process of preparing the quartz surface nanostructure is as follows:

[0033] First, 3 nm of catalytic metal tin was deposited on the quartz surface using thermal evaporation deposition equipment.

[0034] Then, the quartz sample with catalytic metal tin deposited on the surface is transferred to a plasma enhanced chemical vapor deposition system (PECVD) and a nanostructure is prepared using the VLS nanowire growth mode. The specific process includes:

[0035] At 200°C, the hydrogen flow rate was 20 SCCM and the RF power was 10 mW / cm 2 , the chamber pressure is 30Pa, and hydrogen plasma treatment is used for about 5 minutes to reduce the oxide layer on the surface of the tin particles to form catalytic metal particles;

[0036] Then hydrogen and monosilane (SiH 4 ), where the hydrogen flow rate is 60 SCCM, the monosilane flow rate is 6 SCCM, the chamber temperature is 350 ° C, and the RF power density is 20 mW / cm 2 , the chamber pressure is 100 Pa, and the nanostructure growth time is 5 min.

[0037] The quartz sample with silicon nanostructures grown on the surface is transferred to a muffle furnace, the temperature is set to 900°C, and annealed in air for 60 minutes to oxidize the silicon nanostructures. After the annealed quartz sample cools to room temperature, it is taken out and a layer of organic gold coating is brushed on the surface of the quartz sample with a brush. The main component of the organic gold coating is resin acid gold, the solid content is 40wt%, and the solvent is turpentine + pine alcohol (volume ratio is 1:1). The quartz sample brushed with the organic gold coating is allowed to stand for 20 minutes, and then it is transferred to a muffle furnace for annealing, the heating rate is 10°C / min, the temperature is raised to 800°C, and it is maintained for 15 minutes. When the temperature of the quartz sample drops below 100°C, it is taken out, and a gold coating is coated on the surface of the quartz sample.

[0038] Example 2

[0039] The process of preparing the quartz surface nanostructure is as follows:

[0040] First, 3 nm of catalytic metal tin was deposited on the quartz surface using thermal evaporation deposition equipment.

[0041] Then, the quartz sample with catalytic metal tin deposited on the surface is transferred to a plasma enhanced chemical vapor deposition system (PECVD) and a nanostructure is prepared using the VLS nanowire growth mode. The specific process includes:

[0042] At 150°C, the hydrogen flow rate was 15 SCCM and the RF power was 5 mW / cm 2 , the chamber pressure is 20Pa, and hydrogen plasma treatment is used for about 5 minutes to reduce the oxide layer on the surface of the tin particles to form catalytic metal particles;

[0043] Then hydrogen and monosilane (SiH 4 ), where the hydrogen flow rate is 50 SCCM, the monosilane flow rate is 5 SCCM, the chamber temperature is 300 °C, and the RF power density is 15 mW / cm 2 , the chamber pressure is 80Pa, and the nanostructure growth time is 5min.

[0044] The quartz sample with silicon nanostructures grown on the surface is transferred to a muffle furnace, the temperature is set to 900°C, and annealed in air for 50 minutes to oxidize the silicon nanostructures. After the annealed quartz sample cools to room temperature, it is taken out and a layer of organic gold coating is brushed on the surface of the quartz sample with a brush. The main component of the organic gold coating is resin acid gold, the solid content is 40wt%, and the solvent is turpentine + pine alcohol (volume ratio is 1:1). The quartz sample with the organic gold coating is allowed to stand for 10 minutes, and then it is transferred to a muffle furnace for annealing, the heating rate is 10°C / min, the temperature is raised to 750°C, and it is maintained for 10 minutes. When the temperature of the quartz sample drops below 100°C, it is taken out, and a gold coating is coated on the surface of the quartz sample.

[0045] Example 3

[0046] The process of preparing the quartz surface nanostructure is as follows:

[0047] First, 5 nm of catalytic metal tin was deposited on the quartz surface using thermal evaporation deposition equipment.

[0048] Then, the quartz sample with catalytic metal tin deposited on the surface is transferred to a plasma enhanced chemical vapor deposition system (PECVD) and a nanostructure is prepared using the VLS nanowire growth mode. The specific process includes:

[0049] At 250°C, the hydrogen flow rate was 25 SCCM and the RF power was 15 mW / cm 2 , the chamber pressure is 50Pa, and the hydrogen plasma treatment is used for about 10 minutes to reduce the oxide layer on the surface of the tin particles to form catalytic metal particles;

[0050] Then hydrogen and monosilane (SiH 4 ), where the hydrogen flow rate is 70 SCCM, the monosilane flow rate is 10 SCCM, the chamber temperature is 400 °C, and the RF power density is 35 mW / cm 2 , the chamber pressure is 120Pa, and the nanostructure growth time is 10min.

[0051] The quartz sample with silicon nanostructures grown on the surface is transferred to a muffle furnace, the temperature is set to 1000°C, and annealed in air for 100 minutes to oxidize the silicon nanostructures. After the annealed quartz sample cools to room temperature, it is taken out and a layer of organic gold coating is brushed on the surface of the quartz sample with a brush. The main component of the organic gold coating is resin acid gold, the solid content is 40wt%, and the solvent is turpentine + pine alcohol (volume ratio is 1:1). The quartz sample brushed with the organic gold coating is allowed to stand for 30 minutes, and then it is transferred to a muffle furnace for annealing, the heating rate is 10°C / min, the temperature is raised to 850°C, and it is maintained for 15 minutes. When the temperature of the quartz sample drops below 100°C, it is taken out, and a gold coating is coated on the surface of the quartz sample.

[0052] Comparative Example 1

[0053] A layer of organic gold coating is applied on the quartz surface with a brush. The main component of the organic gold coating is resin acid gold, the solid content is 40wt%, and the solvent is turpentine oil + pine alcohol (volume ratio is 1:1). The quartz sample coated with the organic gold coating is left to stand for 20 minutes, and then transferred to a muffle furnace for annealing. The heating rate is 10°C / min, and the temperature is raised to 800°C, and maintained for 15 minutes. When the temperature of the quartz sample drops below 100°C, it is taken out, and the gold coating is applied on the surface of the quartz sample.

[0054] Test Example 1

[0055] The nanostructures prepared in Example 1 were characterized using a scanning electron microscope (SEM). Figure 1 As shown, the results show that the nanostructures are evenly distributed on the surface of the quartz substrate, and the top size of most of the nanostructures is larger than the bottom size, which can form a good mechanical interlocking with the gold coating, thereby improving the adhesion of the gold coating on the quartz surface.

[0056] Test Example 2

[0057] The gold coating structures prepared in Example 1 and Comparative Example 1 were characterized using a scanning electron microscope (SEM). Figure 2 As shown, the results show that the nanostructure on the quartz substrate can effectively improve the microstructure of the gold coating, reduce the pore defects in the gold coating, make the gold coating denser, and help to increase the service life of the gold coating.

[0058] Test Example 3

[0059] The adhesion strength of the gold coating on the quartz surface in Example 1 and Comparative Example 1 was measured using a scratch instrument. The adhesion strength of the coating refers to the strength of the bonding between the coating and the substrate, that is, the energy required to peel off the coating per unit surface area from the substrate (or intermediate coating).

[0060] The results are as follows Figure 3 As shown in the figure, when the load reaches 27mN (millinewton), the gold coating on the quartz surface without the growth of nanostructures begins to detach, which is specifically manifested as a change in the friction coefficient. Combined with the test data, it can be concluded that the adhesion strength of the gold coating on the flat quartz surface without the growth of nanostructures is 20J / m 2 ; The gold coating on the quartz surface with nanostructures did not detach within the test range of the device (load 0-80mN), which is specifically manifested by the fact that the friction coefficient did not change, that is, friction f-load F N The slope of the relationship curve did not change, indicating that after the nanostructure grew on the quartz surface, a strong bonding force was formed between the gold coating on the quartz surface and the quartz substrate, with a greater adhesion strength.

Claims

1. A surface treatment method for enhancing the adhesion of a gold coating on a quartz surface, characterized in that: The steps include: (1) Depositing catalytic metal particles on a cleaned quartz wafer; (2) removing the oxide layer on the surface of the catalytic metal particles on the quartz plate obtained in step (1); (3) using silane gas to grow a silicon nanostructure on the surface of the quartz wafer obtained in step (2); (4) oxidizing the quartz plate obtained in step (3) at high temperature to convert the silicon nanostructure into silicon oxide; (5) coating the organic gold paste on the surface of the quartz plate obtained in step (4); (6) The quartz plate obtained in step (5) is subjected to heat treatment to decompose the organic gold on the surface to form a gold coating.

2. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 1, characterized in that: The catalytic metal in step (1) is one or more of tin, indium, gallium and gold.

3. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 1, characterized in that: In step (1), the catalytic metal is deposited on the quartz plate by thermal evaporation.

4. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 1, characterized in that: The thickness of the catalytic metal film in step (1) is 3-5 nm.

5. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 1, characterized in that: Steps (2) and (3) are performed in a plasma enhanced chemical vapor deposition system.

6. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 1, characterized in that: Process conditions in step (2): temperature 150-250°C, hydrogen flow rate 15-25 SCCM, RF power 5-15 mW / cm 2 , the chamber pressure is 20-50Pa, and the hydrogen plasma treatment time is 5-10min; Process conditions in step (3): hydrogen flow rate is 50-70 SCCM, silane flow rate is 5-10 SCCM, chamber temperature is 300-400°C, and RF power density is 15-35 mW / cm 2 , the chamber pressure is 80-120Pa, and the nanostructure growth time is 5-10min.

7. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 1, characterized in that: In step (4), the temperature of high temperature oxidation is 900-1000° C., and the time is 50-100 min.

8. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 1, characterized in that: The organic gold paste in step (5) comprises resin acid gold, metal additives, resin and solvent, and the organic gold paste is coated on the treated sample surface by brushing or spraying.

9. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 1, characterized in that: The heat treatment method in step (6) is high temperature annealing or infrared heating.

10. The surface treatment method for enhancing the adhesion of gold coating on quartz surface according to claim 9, characterized in that: The heat treatment method in step (6) is high temperature annealing, the high temperature annealing temperature is 750-850°C, the high temperature annealing time is 10-15min, and the heating rate is 10°C / min.

Citation Information

Patent Citations

  • Method for increasing surface etching roughness of quartz plate

    CN104176943A

  • Protected gold coating and process

    EP0237206A2

  • Electromagnetic perfect absorber based on sub-wavelength metallic hole array

    CN101724811A

  • Coating solution for forming alkali barrier layer, and article

    CN104918897A

  • Preparation method of nitrogen dioxide gas sensor of gold-modified vanadium dioxide nanowire

    CN107764872A

Cited By

  • Method for preparing high-conductivity and high-infrared-reflection transparent gold coating through solution method

    CN121377557A